Penyuluhan Kesehatan Tentang Dismenorhea di SMPN 1 Madapangga Kabupaten Bima - Nur Fitriyah N; Nurlaila Fitriani; Ade Sriwahyungsih (PT.Mantaya Idea Batara, 2022)
Adolescents in every country have an important role in the development of the country. Because teenagers are an important asset as the successor to a better generation. To create a better generation, young people must carry out positive activities for their progress. During adolescence, rapid development occurs, causing rapid changes in the process of physical, cognitive and psychosocial growth. Sexual maturity occurs and the achievement of an adult form. In line with physical and psychological changes, adolescents need to know about how to adapt to the changes that occur in themselves. During this period, young women will experience menarche, which is the first menstruation. During this menstrual period, young women will also be able to experience Pre Menstrual Syndrome (PMS). However, especially young women still have many obstacles to carry out their daily activities, because of dysmenorrhea. This service is carried out at SMPN 1 Madapangga. The method of service is by Lectures / counseling, discussions and questions and answers. As a result of the dedication, we got the enthusiasm of active participants in asking questions. Participants said their knowledge increased about dysmenorrhea